Targeting Long Non-Coding RNAs in Hepatocellular Carcinoma: Progress and Prospects - Lin, Xinrong; Xiang, Xiaosong; Feng, Bing; Zhou, Hao; Wang, Ting; Chu, Xiaoyuan; Wang, Rui (Frontiers in Oncology, 2021)
Hepatocellular carcinoma is the fifth ranked cancer worldwide with a relatively low five year survival rate. Long non coding RNAs are a group of RNAs with remarkable aberrant expression which could act on multiple bioprocesses, and ultimately impact upon tumor proliferation, invasion, migration, metastasis, apoptosis and therapy resistance in cancer cells including hepatocellular carcinoma cells. Recent years, long non coding RNAs have been reported to be indispensable targets in clinical target therapy to stop the growth of cancer and prolong the lifespan of patients with hepatocellular carcinoma. In this review, we enumerate the signaling pathways and life activities affected by long non coding RNAs in hepatocellular carcinoma cells to illustrate the role of long non coding RNAs in the development and therapy resistance of hepatocellular carcinoma.